Secularism and the European Court of Human Rights - Gulalp, Haldun (KLUWER LAW INT, 2010)
This article examines the variety of State-religion relations and the place of Islam in Europe through a critical analysis of the case law of the European Court of Human Rights (ECtHR, or the Court). This examination reveals both the patterns of litigation, hence the diversity in national political cultures, and the dominant normative assumptions about religion and secularism in Europe more generally, which are implicit in the Court's reasoning. Although the Court grants a 'margin of appreciation' to individual states, the margin itself seems to vary according to those implicit normative preferences. The essay argues that although neither the Convention nor the Court prescribes a normative model of secularism or State-religion relations, there still seems to be an implicit pattern whereby the Court prefers some models to others. Historically ingrained cultural assumptions about not only the division between Christianity and Islam but also between Western and Eastern Christianity appear to have played a part in the reasoning of the judges of the ECtHR.
Keywords: Government & Law